Integrasi Media dalam Pembelajaran: Pendekatan Konstruktivisme Vygotsky: Media Integration in Learning: Vygotsky's Constructivism Approach - Azis, Abdul; Hilmy, Masdar; Erawati, Desi (Anterior Jurnal, 2025)
Media use in learning has become an integral part of the modern education landscape. Despite the continuous advancements in educational technology, the effectiveness of learning media remains significantly determined by the pedagogical approach employed. One relevant and potentially impactful approach for optimizing media utilization is social constructivism, developed by Lev Vygotsky. This approach emphasizes that learning occurs through social interaction, supported by more competent individuals through the Zone of Proximal Development (ZPD) concepts and scaffolding. This study analyzes how learning media can be effectively integrated through Vygotsky's constructivist approach. The method employed in this research is library research, which reviews various theoretical sources and relevant prior research findings. The results of the review indicate that integrating media based on social constructivism can enhance student engagement, foster collaborative interaction, and strengthen the knowledge construction process. Thus, utilizing media aligned with the principles of Vygotsky's constructivism is a crucial strategy in creating meaningful and contextual learning experiences.